Lifting the veil of incorporation under common law and statute. Issue 1 (4th February 2014) - Nyombi, Chrispas
Abstract : Purpose: – The paper examines case law and statutory provisions related to lifting the corporate veil. The aim of the paper is to explore recent case law in order to determine whether courts have moved away from an overly restrictive approach when dealing with cases relating to the corporate personality. To offer a full account of the exceptions to the corporate personality doctrine, this paper also examines cases where the veil of incorporation is lifted due to a breach of a statutory provision. Design/methodology/approach: – The paper reviews recent case law and statutory provisions relating to lifting the corporate veil. The paper critically reviews the exceptions to the corporate personality doctrine which amount to lifting the corporate veil. Findings: – The paper finds that courts are more willing to lift the corporate veil compared to before. They have moved away from the restrictive approach and this is demonstrated by the tendency to find new exceptions to the corporate personality doctrine such as the interests of justice argument or lifting the veil in tort cases. Originality/value: – The paper offers an up-to-date assessment of the exceptions to the corporate personality doctrine and highlights the growing tendency to finding new ways of lifting the corporate veil.